Supporting employees with chronic conditions to stay at work: perspectives of occupational health professionals and organizational representatives - A. R. Bosma; C. R. L. Boot; N. C. Snippen; F. G. Schaafsma; J. R. Anema (BMC, 2021)
Abstract Background Supporting employees with chronic conditions can prevent work-related problems and facilitate sustainable employment. Various stakeholders are involved in providing support to these employees. Understanding their current practices and experienced barriers is useful for the development of an organizational-level intervention to improve this support. The aim of this study was to explore the current practices of occupational physicians and organizational representatives, identifying both barriers to providing support and opportunities for improvement. Methods Two focus groups with sixteen occupational physicians and seven semi-structured interviews with organizational representatives were held between January and June 2018. Data was analyzed using thematic content analysis. Results Several barriers to offer support were identified, including barriers at the organizational level (negative organizational attitudes towards employees with chronic conditions), the employee level (employees' reluctance to collaborate with employers in dealing with work-related problems), and in the collaboration between occupational physicians and organizational representatives. In addition, barriers in occupational health care were described, e.g. occupational physicians' lack of visibility and a lack of utilization of occupational physicians' support. Opportunities to optimize support included a shared responsibility of all stakeholders involved, actively anchoring prevention of work-related problems in policy and practice and a more pronounced role of the health care sector in preventing work-related problems. Conclusions Preventing work-related problems for employees with chronic conditions can be achieved by addressing the identified barriers to provide support. In addition, both occupational physicians and organizational representatives should initiate and secure preventive support at the organizational level and in occupational health care. These insights are helpful in developing an intervention aimed at supporting employees with chronic conditions to stay at work.